Surgical management of the fourth ventricle arachnoid cysts (Annals of Medical Research, 2021)
Aim: The arachnoid cysts are developmental masses that occur from the splitting or duplication of the arachnoid membrane. They may occur in different locations such as middle cranial fossa, retrocerebellar and convexity region, and they are usually asymptomatic. Arachnoid cysts are uncommon in association with intraventricular location especially fourth ventricle. In this study, we present six consecutive cases with arachnoid cyst in the fourth ventricle.Material and Methods: There were four female and two male patients. The average age of patients was 37 years ranging from2 to 65 years. These patients were periodically followed-up. The follow-up period ranged from minimum 2 to 6 years. Three patients were operated by a ventriculoperitoneal shunt and surgical excision was performed in two patients. Remaining two patients were followed up because they were asymptomatic.Results: Revision surgery was made due to shunt malfunction in a patient. The symptoms had been regressed in all patients. The arachnoid cysts were completely regressed after the operations in two patients.Conclusion: Most of arachnoid cysts which were small and asymptomatic did not require treatment. However, the size of an arachnoid cyst typically remained stable or increased over the time.An asymptomatic cyst may become symptomatic after minor head trauma. So, the asymptomatic patients with fourth ventricle arachnoid cyst should be under periodic follow up for obstructive hydrocephalus. Keywords: Arachnoid Cyst; Fourth Ventricle; Ventriculoperitoneal Shunt; Surgical Excision.
Keywords: Arachnoid Cyst; Fourth Ventricle; Ventriculoperitoneal Shunt; Surgical Excision.